APPLICATION OF BAYESIAN ANALYSIS FOR COMPREHENSIVE ASSESSMENT OF THE STATE OF FISH RESOURCES IN FRESHWATER ECOSYSTEMS - Shapen, K.; Akhmedov, A.; Rakhymova, А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
Water resources, including rivers, lakes and reservoirs, play a key role in maintaining the ecological balance, developing fisheries and preserving biodiversity. To ensure effective management and rational use of water resources, scientific research is conducted annually, including control fishing, which is aimed at determining the permissible catch volumes and developing strategies for preserving the aquatic environment. Within the framework of such studies, special attention is paid to water quality, the state of the food supply and the analysis of fish populations, including species, numbers and age structure. This study uses a Bayesian approach that reveals complex patterns and dynamic changes in ecosystems that remain invisible when using traditional statistical methods. This approach contributes to a deeper understanding of processes occurring in water bodies and to the optimization of fisheries management. Bayesian analysis allows for more accurate predictions of changes in fish populations and their structures, which contributes to improved management of aquatic ecosystems and the conservation of biodiversity.